“LIFELONG LEARNING” PRINCIPLE IN PROFESSIONAL COMPETENCE FORMING PROCESS OF FUTURE DENTISTS - Kulbashna, Ya. (Continuing Professional Education: Theory and Practice, 2019)
There is a crisis of classical idea and educational model in Ukraine, caused by significant changes in country at the end of XX beginning of XXI centuries. It has followed to break off between deeply changed conditions of society’s lifestyle and educational system. Due to this, the necessity of educational system modernisation was arised. The new competentive model in professional training was proposed and introduced in Europe and in Ukraine. One of the most important principle of it is the “lifelong learning”. It must provide increasing of professional level in specialists during all period of professional activity. Such important changes the medical educational system also was concerned. In the article the process of professional competence forming in future dentists among native and foreign students аnd introduction in modern medical education the “lifelong learning” principle is considered. There were 721 future dentists (481 students,114 foreign among them and 235 interns) took part in the investigation. The readiness of future specialists for the increasing the educational level during all period of professional activity is researched. The results show the necessity to force the student’s motivation for understanding and accepting of this principle.